Innovation, productive capacity, training and productivity - Manuel Guisado González; Mercedes Vila Alonso; Manuel Guisado Tato (Management Letters/Cuadernos de Gestión, 2016)
This study analyzes the relationship between labor productivity, radical innovation, incremental innovation, embodied technology in machinery and equipment, utilization of production capacity and training. The data used are from Spanish companies, manufacturing and services, and have been collected by the Business Environment and Enterprise Performance Survey (BEEPS). The technique used to estimate the coefficients of the model is the ordinary least square regression, since the dependent variable (labor productivity) is continuous. The results indicate that radical innovation and training have a significant positive impact on labor productivity. The influence of embodied technology is also significant, but of negative sign. Finally, note that the companies that export and larger achieve higher levels of productivity. The findings of this study have implications for responsible for economic policy. Spanish policy makers should promote and subsidize the purchase of machinery and equipment more efficient for companies that achieve lower levels of productivity, and subsidize the training of workers in the management of these new equipments. They must also promote and subsidize the development of activities high in R&D for companies that achieve high levels of productivity, to increase their performance in radical innovation. The promotion and subsidization of training programs related to R&D is also essential in this type of companies, especially in a scenario characterized by an intense and rapid technological change.